КЛИНИКО-ЛАБОРАТОРНАЯ ХАРАКТЕРИСТИКА ХРОНИЧЕСКИХ ГЕПАТИТОВ И ЦИРРОЗОВ ПЕЧЕНИ РАЗЛИЧНОЙ ЭТИОЛОГИИ - А. Р. Билалова; В. В. Макашова (Архивъ внутренней медицины, 2015)
The review of literature discusses the clinical and biochemical changes in patients with chronic hepatitis C, chronic hepatitis of alcoholic etiology, chronic hepatitis combined genesis (HCV + alcohol) and cirrhosis in the outcome of hepatitis, liver cirrhosis complications.